2007
DOI: 10.1074/jbc.m703485200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Links between the Fusion Peptide-proximal Polar Segment and Membrane-proximal Region of Human Immunodeficiency Virus gp41 in Distinct Phases of Membrane Fusion

Abstract: The binding of CD4 and chemokine receptors to the gp120 attachment glycoprotein of human immunodeficiency virus triggers refolding of the associated gp41 fusion glycoprotein into a trimer of hairpins with a 6-helix bundle (6HB) core. These events lead to membrane fusion and viral entry. The envelope glycoprotein complex (Env) 4 of human immunodeficiency virus type 1 (HIV-1) comprises a trimer of receptor binding gp120 subunits in non-covalent association with a trimer of transmembrane gp41 subunits on the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 97 publications
4
95
2
Order By: Relevance
“…Other authors had shown an interaction between MPER and FPPR during infection [18][19][20][21][22]. These findings suggested that the interaction between the MPER and the FPPR during infection may generate a conformation able to induce 2F5/4E10-like neutralising antibodies.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Other authors had shown an interaction between MPER and FPPR during infection [18][19][20][21][22]. These findings suggested that the interaction between the MPER and the FPPR during infection may generate a conformation able to induce 2F5/4E10-like neutralising antibodies.…”
Section: Discussionmentioning
confidence: 67%
“…There may be several reasons for the failure of many of the attempts to induce 2F5/4E10-like neutralising antibodies including our new approach: First, although it has been shown, that peptides derived from the FPPR increase the binding of mAb 2F5 to its epitope in the MPER/ E2 domain [14] and there is an interaction between MPER and FFPPR [18][19][20][21][22], it is still unknown whether this interaction is also required for the induction of 2F5/4E10-like broadly neutralising antibodies. Second, it remains unclear, whether the DNA immunisation generated the correct membrane associated context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the MPER in fusion is further supported by the ability of three bNt MAbs (2F5, 4E10, and Z13) to recognize epitopes in this region; thus binding to the MPER by these MAbs blocks infection, presumably by interfering with one of the critical steps required for viral entry. A recent study evaluated the crucial role of the FP-proximal PR and the MPER during HIV-1 infection using two different modes of viral transmission: cell-to-cell and virus-to-cell fusion (13). Interestingly, Ala substitution of Trp 666 , Trp 672 , Phe 673 , and Ile 675 in the MPER reduced viral entry potential by ϳ120-fold without affecting cell-to-cell fusion.…”
Section: Role Of the Mper In Fusionmentioning
confidence: 99%
“…[41][42][43][44][45] In addition we had shown that the binding of 2F5 is enhanced when in addition to the peptide containing its epitope a peptide corresponding to the FPPR is present, suggesting that the interaction between both peptides induces a conformation allowing a better binding of 2F5. 46 Whether this conformation is also required to induce broadly neutralizing antibodies remains unclear.…”
Section: Immunisation With Hybrid Proteinsmentioning
confidence: 99%